Utilization Of Coconut Coir Waste to Encourage a Green Economy in Simbang Village, Majene Regency (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
This community service activity aims to increase the capacity of the community in processing coconut coir waste into products of economic value such as brooms, flower pots, brushes and mining ropes. Organic waste management, especially coconut coir, has great potential in supporting sustainable economic development based on a green economy at the village level. Simbang Village, Pamboang District, Majene Regency, is one of the coconut-producing areas with a fairly high volume of coir waste but has not been utilized optimally. The implementation method includes socialization, technical training to 25 participants who will later become a coconut fiber processing business group at the village level, assistance to business groups, as well as monitoring and evaluation. The results of the activity show that the community is beginning to understand the economic value of coconut fiber waste and show enthusiasm in developing its processing business. This activity also succeeded in forming a new business group that initiated small-scale household production. With a participatory and empowerment approach, this activity has a positive impact on environmental awareness and economic independence of the community. This service is expected to be a model for green economy development based on local potential in Majene Regency